Disability, Urban Health Equity, and the Coronavirus Pandemic: Promoting Cities for All - Pineda, Victor Santiago (J Urban Health, 2020)
Persons with disabilities (PWDs) living in cities during the COVID-19 pandemic response may be four times more likely to be injured or die than non-disabled persons, not because of their “vulnerable” position but because urban health policy, planning and practice has not considered their needs. In this article, the adverse health impacts on PWDs during the COVID-19 pandemic reveals the “everyday emergencies” in cities for PWDs and that these can be avoided through more inclusive community planning, a whole-of-government commitment to equal access, and implementation of universal design strategies. Importantly, COVID-19 can place PWDs at a higher risk of infection since some may already have compromised immune and respiratory systems and policy responses, such as social distancing, can lead to life-threatening disruptions in care for those that rely on home heath or personal assistants. Living in cities may already present health-damaging challenges for PWDs, such as through lack of access to services and employment, physical barriers on streets and transportation, and smart-city technologies that are not made universally accessible. We suggest that the current pandemic be viewed as an opportunity for significant urban health reforms on the scale of the sanitary and governance reforms that followed ninetieth century urban epidemics. This perspective offers insights for ensuring the twenty-first century response to COVID-19 focuses on promoting more inclusive and healthy cities for all.